2015
DOI: 10.2341/13-310-l
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Tensile Retention of Y-TZP Crowns Cemented on Resin Composite Cores: Effect of the Cement and Y-TZP Surface Conditioning

Abstract: This study evaluated the effect of the cement type (adhesive resin, self-adhesive, glass ionomer, and zinc phosphate) on the retention of crowns made of yttria-stabilized polycrystalline tetragonal zirconia (Y-TZP). Therefore, 108 freshly extracted molars were embedded in acrylic resin, perpendicular to their long axis, and prepared for full crowns: the crown preparations were removed and reconstructed using composite resin plus fiber posts with dimensions identical to the prepared dentin. The preparations wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 28 publications
2
20
0
Order By: Relevance
“…However, band is unaesthetic in the anterior, which requires esthetic compared with the posterior, and may irritate the gingiva. Thus, there is a great interest in developing methods for maintaining bonded brackets directly on restoratives, and appropriate surface treatment methods have been devised [17,18,19]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, band is unaesthetic in the anterior, which requires esthetic compared with the posterior, and may irritate the gingiva. Thus, there is a great interest in developing methods for maintaining bonded brackets directly on restoratives, and appropriate surface treatment methods have been devised [17,18,19]. …”
Section: Discussionmentioning
confidence: 99%
“…As surface treatment methods become more complicated, the clinical application of these methods become more difficult, which means that finding a simple method to enhance the bond strength becomes imperative. To increase the bond strength, a variety of surface treatments [17,18,19] such as rough polishing, sandblasting with high strength particles, glass coating, acid etching, laser treatment, and primer treatments have been reported [14,20,21,22,23]. …”
Section: Introductionmentioning
confidence: 99%
“…Different pretreatments (chemical, mechanical or both) for implant surfaces in contact with the cement line have been proposed in other studies. 15,16,17 Studies on the strength of cemented crowns with different roughness after treatment with aluminum oxide revealed that smooth surfaces show less tensile strength than those with grooves or roughness and that the topography of the prosthetic abutment can increase resistance. 18 In the present study, exposure to phosphoric acid increased the opacity and porosity of the metal surface.…”
Section: Discussionmentioning
confidence: 99%
“…Representative images were taken with a scanning electronic microscope (SEM) (JSM-6360LV, JEOL USA, Inc., Peabody, MA, USA). This classification was adapted from Amaral et al 4 and Rippe et al 6 .…”
Section: Failure Analysismentioning
confidence: 99%
“…During the clinical treatment with prosthetics, dentists will often use provisional restorations in patients before permanent restoration can be performed. During this period, the composite core build-up can be exposed to moisture, variances in pH and temperature 6 and temporary luting cements 7 . As a result, surface alterations of the composite core could be required to improve their adhesion to resin cements and for optimal crown retention 6 .…”
Section: Introductionmentioning
confidence: 99%